Upward Flame Spread and Extinction over Wavy Solids. Issue 7 (2nd July 2020) - Stalcup, Erik J.; T'ien, James S.; Jordan, Jonathan; Wu, Zhengxuan; Nastac, Gabriel; Li, Chengyao
ABSTRACT: Laboratory scale experimental and modeling results of one-sided upward flame spread over wavy cellulosic paper samples are presented. The sinusoidal shaped samples with varying wavelength and amplitude are aligned perpendicular to the gravitational direction so the upward buoyant flow sees peaks and valleys along its flow path. Depending on the wave amplitude and wavelength, the flame can spread from sample peak to peak initially but may later sustain slow burning from isolated flamelets inside the sample valleys or become quenched. The degree of fuel burning completeness, pyrolysis front spread rate, and extinction limits (both local and overall) depend on the wavy parameters in a complex way as well as the ambient relative humidity. Flame spread over wavy samples thus has unique features not found in continuous flat samples nor in discrete samples. Video records of the experiments supplied in the paper present both the front and the side views of these interesting transient flame developments. A simplified two-dimensional numerical model was formulated and solved to show selected salient features of the complex fluid dynamics over wavy structure and the heat transfer and burning characteristics of the wavy samples.